2016
DOI: 10.1002/ange.201600590
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Shielding in an Enzyme‐thin and Soft Organosilica Layer

Abstract: The fragile nature of most enzymes is am ajor hindrance to their use in industrial processes.H erein, we describe as ynthetic chemical strategy to produce hybrid organic/inorganic nanobiocatalysts;i te xploits the self-assembly of silane building blocks at the surface of enzymes to grow an organosilica layer,ofcontrolled thickness,that fully shields the enzyme.Remarkably,the enzyme triggers arearrangement of this organosilica layer into asignificantly soft structure.W e demonstrate that this changei ns tiffnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Concomitantly, AP activity dropped from 90±1.2 U g −1 (U per gram of SNPs) to 11±0.2 U g −1 . This loss in activity was consistent with our previous results, where we demonstrated that a curing phase is necessary to recover enzymatic activity through reorganization of the protective organosilica layer . Accordingly, the particles were incubated at 25 °C for 24 h for the curing reaction.…”
Section: Figuresupporting
confidence: 92%
“…Concomitantly, AP activity dropped from 90±1.2 U g −1 (U per gram of SNPs) to 11±0.2 U g −1 . This loss in activity was consistent with our previous results, where we demonstrated that a curing phase is necessary to recover enzymatic activity through reorganization of the protective organosilica layer . Accordingly, the particles were incubated at 25 °C for 24 h for the curing reaction.…”
Section: Figuresupporting
confidence: 92%
“…Following the immobilization of AuNR–IgG bioconjugates on glass substrates, a polymer encapsulation layer is formed through copolymerization of (3-aminopropyl) trimethoxysilane (APTMS) and trimethoxy­(propyl)­silane (TMPS) on AuNR and around immobilized IgG. The methoxy group of TMPS and APTMS undergoes rapid hydrolysis to form methanol and trisilanols. , Hydrolysis is followed by condensation of the silanols, which results in the formation of an amorphous aminopropyl functional polymer layer consisting of Si–O–Si bonds and functional end groups such as hydroxyl (−OH), amine (−NH 3 + ), and methyl (−CH 3 ). , These end groups interact noncovalently via hydrogen bonding, hydrophobic, and electrostatic interactions with AuNR–IgG bioconjugates resulting in the formation of a stable organosilica layer around them. Next, bifunctional PEG (methoxy-PEG-silane) was covalently grafted on to the free regions of the organosilica layer.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve a thin polymer encapsulation, 0.4 μL of TMPS and 0.4 μL of APTMS were added to 1 mL of the AuNR–PA–IgG bioconjugate solution under gentle stirring at room temperature for 30 min and then left overnight at 4 °C. , The thickness of the encapsulation layer can be controlled by varying the volume of TMPS and APTMS added to the bioconjugate solution and can be monitored via LSPR wavelength shifts measured with a ultraviolet–visible (UV–vis) spectrophotometer. After that, the solution was centrifuged at 8000 rpm for 10 min to remove free polymers and then resuspended in 1× PBS for further usage.…”
Section: Methodsmentioning
confidence: 99%
“…This not only restricts the printability of these bioinks without compromising their functionality but also leads to limited stability and short shelf life of the printed biosensors. Most recent progress in preserving the biofunctionality of biosensor chips involves coating the entire chips with protective materials, such as metal–organic frameworks and organosiloxane. However, these approaches are limited to immobilized bionanoconjugates on rigid substrates and not compatible with printing processes. Realization of ultrastable bionanoconjugate inks that are resistant to harsh conditions remains challenging.…”
mentioning
confidence: 99%